2018
DOI: 10.1097/md.0000000000009869
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous retroperitoneal hemorrhage in Menkes disease

Abstract: Rationale:Menkes disease (MD), also known as Menkes kinky hair disease, is a fatal neurodegenerative disease caused by a defect in copper metabolism. The symptoms involve multiple organ systems, such as the brain, lung, gastrointestinal tract, urinary tract, connective tissue, and skin. There is currently no cure for this disease entity, and patients with the classic form of MD usually die from complications between 6 months and 3 years of age. Intracranial hemorrhage secondary to tortuous intracranial arterie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…RPH may occur during pregnancy and puerperium as a result of rupture of one of the retroperitoneal arteries and also because of coagulation disorders, Ehlers Danlos syndrome and hepatic rupture [2][3][4][5]. Although RPHs occur mostly after trauma, they may also develop spontaneously.…”
Section: Discussionmentioning
confidence: 99%
“…RPH may occur during pregnancy and puerperium as a result of rupture of one of the retroperitoneal arteries and also because of coagulation disorders, Ehlers Danlos syndrome and hepatic rupture [2][3][4][5]. Although RPHs occur mostly after trauma, they may also develop spontaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Jankov et al 5 reported a similar case of a male neonate who also presented in extremis due to rupture of an iliac aneurysm with no prior diagnosis of MD. Peng et al 6 described the case of a 4-year-old boy with a known diagnosis of MD, who presented with spontaneous retroperitoneal hemorrhage secondary to bleeding of multiple friable and tortuous abdominal blood vessels. In the first 2 cases, the unusual and acute nature of the presentations combined with, perhaps, limited awareness made the diagnosis of MD unclear until autopsy examination and genetic examination confirmed the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Color Doppler ultrasonography can also be used to map blood vessels and assess blood flow within them. 6 Computed tomography (CT) and/or magnetic resonance imaging (MRI) angiography can then be considered, as they provide further detail; however, CT involves irradiation and MRI is not as widely available as US or CT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LMAN1 receptor complex defects cause combined FV+VIII deficiency and mild coagulation disorder [ 90 ], underlining importance of mannose binding lectins in glycosylated protein trafficking. LMAN1 is a collectin requiring LOX activation, and in MNK low hepatic copper can affect maturation and trafficking leading to mild clotting deficiency [ 91 ].…”
Section: Redox Shifting Enzymesmentioning
confidence: 99%